Studies of the genus Anthelephila Hope (Coleoptera: Anthicidae) 14. Twenty-four new species from Asia and new records of A. fossicollis Kejval - Kejval, Zbyněk (Zootaxa, 2017)
In this paper twenty-four species of Anthelephila Hope, 1933 are newly described: A. abnormis sp. nov. (Cambodia, Thailand, Vietnam), A. ailani sp. nov. (Laos), A. akela sp. nov. (China, Laos, Thailand), A. alamea sp. nov. (Burma, Laos), A. arcana sp. nov. (Laos), A. ayutthaya sp. nov. (Laos, Thailand), A. banhuaipo sp. nov. (Thailand), A. bannape sp. nov. (Thailand), A. bifida sp. nov. (Thailand), A. bolavensis sp. nov. (Laos), A. davita sp. nov. (Thailand), A. disparilis sp. nov. (Burma, Laos, Thailand, Vietnam), A. falcata sp. nov. (Vietnam), A. fallax sp. nov. (China, Laos, Thailand), A. insolita sp. nov. (Thailand), A. keahi sp. nov. (Laos), A. keilana sp. nov. (Laos), A. kubani sp. nov. (Laos), A. laopako sp. nov. (Laos), A. paucula sp. nov. (Laos, Thailand), A. provecta sp. nov. (Thailand), A. theravada sp. nov. (Burma), A. triplex sp. nov. (Thailand), and A. wanika sp. nov. (Laos). The Anthelephila fossicollis species-group is defined, and other species placed in existing species-groups where previously defined. Anthelephila fossicollis Kejval, 2002 is newly recorded from Sichuan and Tibet.